Legal shape of the Episcopal Conference of Poland - DYDUCH, JAN (Prawo Kanoniczne, 2013)
The Episcopal Conference of Poland, which traces its beginning back to the time of the partitions of Poland, has been shaped by regulations given at the Second Vatican Council and by other Church documents. These documents and regulations have laid the foundation for the statutes of the Episcopal Conference, in particular for the current ones from March 10, 2009. The 2009 Statutes determine the structure, competences and goals of the Episcopal Conference. The Conference is a collegial organ, which consists of bishops canonically connected with territory of Poland and organizes nationwide pastoral care and apostolate.